ALOKASI KEBUTUHAN ALAT BERAT PADA PEKERJAAN NORMALISASI MUARA SUNGAI SIBELIS KOTA TEGAL - Fandi Azhim; Suhariyanto ,; Burhamtoro , (Prokons: Jurnal Teknik Sipil, 2019)
The estuary of River Sibelis is vessel traffic modes of fishermen and the risk rob flooding. The estuary of River Sibelis (STA 0+00 – STA 0+373) project employed some heavy equipment to undertake the project. The purpose of  find out the needs of heavy equipment, productivity of heavy equipment, the duration of work and heavy equipment operational cost. The required data were of layouts, cross sectional drawings of the river estuary, and specifications of heavy equipment. Microsoft Excel program was applied for the calculation and the schedule using method Barchart.The implementation results are as follow: 1) exavating sediment on 29 work days using 1 unit of crane barge in productivity of 80.8 m3/h at Rp. 1.120.384.700,- ; 2) excavating sediment on 16 work days using 2 units of backhoe, 2 units of barge, and 1 unit of tug boat in productivity of 48 m3/h at Rp.351.309,- ; 3) setting sheet pile on 33 work days using 2 units of crawler crane, 1 unit of diesel hammer, 1 unit of tug boat, and 2 units of barge in productivity of 11 m/h at Rp. 805.385.500,-; at total cost project of  Rp. 2.846.349.000,- on  63 work days. Keywords: heavy equipment, productivity, time, cost